2004
DOI: 10.1590/s1806-37132004000500009
|View full text |Cite
|
Sign up to set email alerts
|

O escarro induzido no diagnóstico das doenças pulmonares em pacientes positivos ao vírus da imunodeficiência humana

Abstract: INTRODUÇÃO: O escarro induzido é utilizado para monitorar a inflamação de vias aéreas, porém seu papel como ferramenta diagnóstica de doenças pulmonares em pacientes imunocomprometidos ainda necessita de melhor definição. OBJETIVOS: Determinar o rendimento do escarro induzido no diagnóstico das doenças pulmonares em pacientes positivos ao virus da imunodeficiência humana (HIV). MÉTODO: No período de janeiro de 2001 a setembro de 2002, foram avaliados todos os pacientes com idade superior a 14 anos, infectados … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…8 It is estimated that 65% of the patients infected with HIV present with pulmonary involvement as their first clinical manifestation, and that approximately 80% of HIV-positive patients develop pulmonary disease over the course of the HIV infection. 9 Among various opportunistic infections, respiratory infections account for up to 70% of AIDS-defining illnesses. 10 In Nepal, lower respiratory tract infections (LRTIs) are increasingly reported as opportunistic infections.…”
Section: Introductionmentioning
confidence: 99%
“…8 It is estimated that 65% of the patients infected with HIV present with pulmonary involvement as their first clinical manifestation, and that approximately 80% of HIV-positive patients develop pulmonary disease over the course of the HIV infection. 9 Among various opportunistic infections, respiratory infections account for up to 70% of AIDS-defining illnesses. 10 In Nepal, lower respiratory tract infections (LRTIs) are increasingly reported as opportunistic infections.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that HIV-positive patients are unable to produce a quantity of spontaneous sputum that is sufficient for testing. (27) Anemia is a common finding in patients with tuberculosis. In one study, (28) the prevalence of anemia among tuberculosis patients was reported to be 31.9%.…”
Section: Discussionmentioning
confidence: 99%
“…(7,8,(10)(11)(12)(13)(14)23,24) Anderson et al (8) compared a single IS sample with BAL specimens in HIV-negative patients and also reported low sensitivity for AFB smear testing using both techniques (19% and 12%, respectively), although the sensitivity of culture was 73% in IS and 87% in BAL fluid. Another group of authors (11) demonstrated higher sensitivity for AFB smear testing, comparing 3 IS samples with BAL specimens, and found no difference between HIV-negative and HIV-positive patients (34% and 36% for IS, and 38% and 40% for BAL fluid, respectively).…”
Section: Discussionmentioning
confidence: 99%